Porous‐membrane‐protected polyaniline‐coated SBA‐15 nanocomposite micro‐solid‐phase extraction followed by high‐performance liquid chromatography for the determination of parabens in cosmetic products and wastewater. Issue 7 (10th March 2015) - Ara, Katayoun Mahdavi; Pandidan, Sara; Aliakbari, Azam; Raofie, Farhad; Amini, Mostafa M.
<x xml:space="preserve">Abstract</x> A SBA‐15/polyaniline para‐toluenesulfonic acid nanocomposite supported micro‐solid‐phase extraction procedure has been developed for the extraction of parabens (methylparaben, ethylparaben, and propylparaben) from wastewater and cosmetic products. The variables of interest in the extraction process were pH of sample, sample and eluent volumes, sorbent amount, salting‐out effect, extraction and desorption time, and stirring rate. A Plackett–Burman design was performed for the screening of variables in order to determine the significant variables affecting the extraction efficiency. Then, the significant factors were optimized by using a central composite design. The optimum experimental conditions found at 50 mL sample solution, extraction and desorption times of 40 and 20 min, respectively, 500 μL of 3% v/v acetic acid in methanol as eluent, 0.01 M salt addition, and 10 mg of the sorbent. Under the optimum conditions, the developed method provided detection limits in the range of 0.08–0.4 ng/mL with good repeatability (RSD% < 7) and linearity (r2 = 0.997–0.999) for the three parabens. Finally, this fast and efficient method was employed for the determination of target analytes in cosmetic products and wastewater, and satisfactory results were obtained.